Molecular Classification Trail of Colorectal Cancer Using Immunohistochemical Markers - Mohamed, Amany Mahmoud; Mohamed Fadel, Sabah Ahmed; Ali Wahdan, Mohamed Mostafa; Hedia Mohamed, Abdallah; Ameen Taher, Mahmoud Gamal (Journal of Neonatal Surgery, 2025)
Colorectal cancer (CRC), the third most common and second deadliest malignancy worldwide, is primarily composed of adenocarcinomas and exhibits notable genetic, molecular, and histopathological heterogeneity. Its progression involves chromosomal instability, microsatellite instability, and CpG island methylation, with major genetic contributors including APC, TP53, and KRAS mutations. Risk factors range from hereditary syndromes and inflammatory bowel diseases to dietary and environmental exposures. CRC is classified into four consensus molecular subtypes (CMS): CMS1 (hypermutated, immune-rich), CMS2 (epithelial, chromosomally unstable), CMS3 (epithelial, KRAS-mutated, metabolic), and CMS4 (mesenchymal, invasive, with poor prognosis). Histologically, CRC tumors exhibit features such as tumor budding, tumor-infiltrating lymphocytes (TILs), tumor deposits (TDs), perineural invasion (PNI), and lymphovascular invasion (LVI), all of which impact prognosis and therapeutic response. The epithelial-mesenchymal transition (EMT) plays a crucial role in tumor progression, metastasis, and resistance, marked by loss of E-cadherin and nuclear β-catenin localization alongside vimentin expression. Immunohistochemistry (IHC) aids in molecular classification using markers such as CDX2, CK20, CK7, β-catenin, vimentin, and E-cadherin. High vimentin and nuclear β-catenin correlate with poor survival, while E-cadherin loss predicts invasiveness and poor outcomes. EMT-regulated gene signatures and tumor microenvironment components, particularly cancer-associated fibroblasts and macrophages, further influence tumor behavior and therapeutic resistance. Accurate subtyping using IHC panels provides a cost-effective alternative to transcriptomic profiling, enhancing prognostication and guiding individualized therapy. Integrating molecular, histological, and immunohistochemical features strengthens CRC classification, enabling more precise staging, prognostication, and treatment planning. The review aims to demonstrate how immunohistochemical markers can be used to classify colorectal cancer into molecular subtypes for improved diagnosis, prognosis, and personalized treatment